2013
DOI: 10.1371/journal.pone.0053552
|View full text |Cite
|
Sign up to set email alerts
|

Forced Sexual Experiences as Risk Factor for Self-Reported HIV Infection among Southern African Lesbian and Bisexual Women

Abstract: Even though women who have sex with women are usually understood to be at no or very low risk for HIV infection, we explored whether lesbian and bisexual women in a geographical area with high HIV prevalence (Southern Africa) get tested for HIV and whether, among those women who get tested, there are women who live with HIV/AIDS. The study was conducted in collaboration with community-based organizations in Botswana, Namibia, South Africa and Zimbabwe. Data were collected via written surveys of women who in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 40 publications
3
60
0
Order By: Relevance
“…Discussion This is the first study to report on sexual and reproductive health issues among WSW living in Kenya. As was found in other studies among WSW in Africa, 14,19 women who have sex with women seldom do so exclusively: a substantial proportion of women had sex with men as well, exposing them to all risks associated with heterosexual sex. One out of seven women reported ever having an abortion and one out of three women reported having had at least one STI.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Discussion This is the first study to report on sexual and reproductive health issues among WSW living in Kenya. As was found in other studies among WSW in Africa, 14,19 women who have sex with women seldom do so exclusively: a substantial proportion of women had sex with men as well, exposing them to all risks associated with heterosexual sex. One out of seven women reported ever having an abortion and one out of three women reported having had at least one STI.…”
Section: Resultssupporting
confidence: 61%
“…Furthermore, it is not clear whether the findings are generalizable to all Kenyan WSW (subject recruitment occurred through community organizations; women who could not communicate in English were excluded from participating; and sampling was not random and only took place in the three biggest cities in Kenya). The fact that most women in this study were young (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) suggests that the representativeness of the sample is, indeed, limited.…”
Section: Resultsmentioning
confidence: 95%
“…All four WSW in a participatory action research project in South Africa had been raped, 28 while from 31.1%-33.3% of WSW in two multi-national studies reported forced sex by men or women. 25,26 WSW who had experienced forced sex were more likely to be HIV-positive. 26 Data on the following risk behaviors were also reported: transactional sex (18.6%); 26 condom use in last sexual encounter with male partners (48.0%); 27 and having both male and female partners in the past year (40.0%).…”
Section: Sub-saharan Africamentioning
confidence: 99%
“…Four studies surveyed WSW about male partners: 47.2%-80.0% had ever had sex with men; [24][25][26] nearly 20% reported sex with a man in the past year; 26 and 8.1%-26.3% had ever been married. [25][26][27] Three studies reported data on forced sex. All four WSW in a participatory action research project in South Africa had been raped, 28 while from 31.1%-33.3% of WSW in two multi-national studies reported forced sex by men or women.…”
Section: Sub-saharan Africamentioning
confidence: 99%
“…A 1999 report from the American Institute of Medicine, which evaluated the strength of existing research on the physical and mental health of lesbian women, suggested that 'misconceptions about risk … can negatively affect both the ability of lesbians to seek health care and access treatment' . [2] In South Africa (SA), we know that 10% of women who identify themselves as lesbian or bisexual or have occasional sex with women are infected with HIV, [3] but this knowledge is not usually included in infectious disease education. Women who have sex with women (WSW) are not mentioned in the Department of Health's current National Strategic Plan for HIV, TB and STIs.…”
mentioning
confidence: 99%